2010
DOI: 10.1149/1.3367208
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Synthesis and Characterization of Group IV Nanocrystals

Abstract: The first reports that nanostructured silicon emits radiation in the visible wavelength date back twenty years. This observation is interesting from a fundamental point of view and is potentially important for device engineering, as it points to the opportunity of combining microelectronics and optoelectronics on the same silicon chip. This combination is becoming increasingly attractive due to the intrinsic limitations that are being met by the microelectronics industry in its attempt to progressively reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…In this graph, it is observed that the maximum PL is obtained with Si-NCs of about 2.9 nm in size. Similar results have been reported with 2.6 nm-sized Si-NCs embedded in silicon-rich oxide films deposited by LPCVD [63]. Additionally, a quenching of the PL was obtained for Si-NCs bigger than 4 nm.…”
Section: Resultssupporting
confidence: 89%
“…In this graph, it is observed that the maximum PL is obtained with Si-NCs of about 2.9 nm in size. Similar results have been reported with 2.6 nm-sized Si-NCs embedded in silicon-rich oxide films deposited by LPCVD [63]. Additionally, a quenching of the PL was obtained for Si-NCs bigger than 4 nm.…”
Section: Resultssupporting
confidence: 89%